2022
DOI: 10.1002/jts.22800
|View full text |Cite
|
Sign up to set email alerts
|

Estimating posttraumatic stress disorder severity in the presence of differential item functioning across populations, comorbidities, and interview measures: Introduction to Project Harmony

Abstract: Multiple factor analytic and item response theory studies have shown that items/symptoms vary in their relative clinical weights in structured interview measures for posttraumatic stress disorder (PTSD). Despite these findings, the use of total scores, which treat symptoms as though they are equally weighted, predominates in practice, with the consequence of undermining the precision of clinical decision‐making. We conducted an integrative data analysis (IDA) study to harmonize PTSD structured interview data (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Lastly, our findings identifying evident differences by raceethnicity across key study constructs (i.e., mindfulness, emotion dysregulation, and craving) may also be a function of the psychometric properties of the utilized scales. Recent studies have revealed significant differences in item functioning across scales assessing affect and trauma among underserved groups such as racial and ethnic minoritized populations (i.e., the Clinician-Administered PTSD Scale for DSM-IV (CAPS-IV; Ruglass et al, 2020;Morgan-López et al, 2022) Future studies are needed to examine if these similar psychometric issues are present in other widely used scales such as those utilized in the present study. Indeed, these differences may likely have implications for treatment interventions that target racial-ethnic minoritized groups with substance use dependence.…”
Section: Moderating Effects Of Mindfulness Dispositionmentioning
confidence: 95%
“…Lastly, our findings identifying evident differences by raceethnicity across key study constructs (i.e., mindfulness, emotion dysregulation, and craving) may also be a function of the psychometric properties of the utilized scales. Recent studies have revealed significant differences in item functioning across scales assessing affect and trauma among underserved groups such as racial and ethnic minoritized populations (i.e., the Clinician-Administered PTSD Scale for DSM-IV (CAPS-IV; Ruglass et al, 2020;Morgan-López et al, 2022) Future studies are needed to examine if these similar psychometric issues are present in other widely used scales such as those utilized in the present study. Indeed, these differences may likely have implications for treatment interventions that target racial-ethnic minoritized groups with substance use dependence.…”
Section: Moderating Effects Of Mindfulness Dispositionmentioning
confidence: 95%
“…Notably, there is no particular prioritization of any one symptom over any other symptom within each PTSD criterion, as each symptom is treated as though it has equal priority in reflecting underlying PTSD severity and diagnosis. However, it has been noted that symptom counts can give a distorted picture of underlying disorder severity, because the relative weight of each symptom in relation to the disorder is not taken into account (He et al., 2014; Morgan‐López, Hien et al., 2022; Silverstein et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been long understood that total scores can be problematic from a psychometric perspective (McNeish & Wolf, 2020) as well as a clinical perspective (Saavedra et al., 2022; Saavedra, Morgan‐López, Hien, Back et al., 2021). Total scoring is primarily thought of as a “data management problem”, often with little‐to‐no consideration for what is implied psychometrically by its use (Morgan‐López, Hien et al., 2022; Morgan‐López, Saavedra et al., 2022). For any latent variable model that is structured under the “equal weights” model (e.g., 1‐parameter logistic item response theory (IRT), nonlinear factor analysis [NLFA] with equal factor loadings), the total score is a sufficient statistic for maximum likelihood estimation of the latent variable (Andrich, 1978, 2018; McNeish & Wolf, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations